Evaluation of an adaptive directional system in a DSP hearing aid. - Bentler RA; Tubbs JL; Egge JLM; Flamme GA; Dittberner AB (American Journal of Audiology, 2004)
The effectiveness of an adaptive directional microphone design, as implemented in the Phonak Claro behind-the-ear hearing aid, is evaluated. Participants were fit bilaterally and tested in 2 environments, an anechoic chamber and a moderately reverberant classroom, with the microphones in the fixed (cardioid) setting and the adaptive setting. Five speakers were placed between 110 degrees and 250 degrees azimuth around the listener. Speech-weighted noise was presented from those speakers at an overall level (OAL) of 65 dB (A). Noise was increased by 8 dB from 1 speaker at a time, using 2-s modulation and random assignment, while the output from the other speakers was reduced to maintain the constant OAL. Results of 2 speech perception tasks used as outcome measures indicated that the adaptive system was not able to follow the dominant noise source in the presence of lower level noise sources. Self-report measures obtained after blinded home trials were consistent with laboratory findings that the participants did not perceive this adaptive microphone design to be more effective than the default fixed-microphone option.